Usability Testing of Mobile Online Clinic Booking System for UUM Health Center - Maatug, Aimen A. M. (2009)
The wireless technology is the most interesting technology in the ICT industry today. Mobile devices such as smart phones and personal digital assistants are becoming more commonly used due to the reduction in their size and increase of computational power. In addition, wireless network hotspots (in airports, hotels and commercial outlets) are now beginning to populate the environment. With these advances, new types of mobile applications are becoming available to support users on the move. The mobile environment presents a number of challenges to application developers (including frequent network disconnection and variable bandwidth); therefore mobile Online Clinic Booking System for UUM Health Center was studied in this project with the objective of enhancing the development process of distributed mobile applications. A usability test was conducted and has proved that such technology is highly recommended in an institution as UUM whereby there are a huge number of students.